Pengembangan Media Pembelajaran Berbasis Augmented Reality pada Mata Pelajaran Informatika Kelas VIII di SMPN 1 Karangan - Rahayu Ningsih, Sabila; Nurfirdaus, Nunu (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to develop and determine the feasibility of learning media in the form of a monopoly-type board game based on the surrounding environment created using the Canva application for Pancasila Education learning. This study uses the Research and Development (R&D) method by adapting the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Data were collected through validation sheets from material experts and media experts as well as teacher and student response questionnaires. The results showed that the developed media obtained a feasibility percentage of 93% from material experts and 86% from media experts. In addition, teacher responses reached 88% and student responses were 82%, which indicates that the media is in the very feasible category and received a positive response from users. Based on these results, the developed environmental-based monopoly game media can be used as an alternative learning media for Pancasila Education that is relevant to students' lives. The use of this media has the potential to help teachers deliver learning that is more contextual, interactive, and relevant to students' experiences. Furthermore, the research findings can serve as a basis for developing similar learning media with different materials and environmental contexts.